2018
DOI: 10.1021/acsanm.8b00041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Solution Properties on Iodine Monobromide Doping for Enhanced Bulk Carbon Nanotube Electrical Conductivity

Abstract: Purified commercially available carbon nanotube (CNT) sheet and yarn materials were chemically doped in solutions of IBr using varying solvents to enhance the CNT bulk electrical conductivity. Time-dependent optical absorption spectroscopy was employed to quantify IBr adsorption onto the CNT samples, and results correlate dopant adsorption with CNT conductivity enhancement. Two independent solvent systems were evaluated (hexanes and ethanol) leading to 40% greater conductivity for CNTs doped with IBr in hexane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The development of improved carbon-based electrical conductors for wires and cabling, , integrated circuits, , chemiresistive sensing, , and other applications is the focus of much recent research. Experimental research has demonstrated the potential of some carbon-based conductors to achieve mass specific conductivities which exceed that of copper .…”
Section: Introductionmentioning
confidence: 99%
“…The development of improved carbon-based electrical conductors for wires and cabling, , integrated circuits, , chemiresistive sensing, , and other applications is the focus of much recent research. Experimental research has demonstrated the potential of some carbon-based conductors to achieve mass specific conductivities which exceed that of copper .…”
Section: Introductionmentioning
confidence: 99%